2017
DOI: 10.1037/rev0000062
|View full text |Cite
|
Sign up to set email alerts
|

From anomalies to forecasts: Toward a descriptive model of decisions under risk, under ambiguity, and from experience.

Abstract: Experimental studies of choice behavior document distinct, and sometimes contradictory, deviations from maximization. For example, people tend to overweight rare events in oneshot decisions under risk, and to exhibit the opposite bias when they rely on past experience.The common explanations of these results assume that the contradicting anomalies reflect situation-specific processes that involve the weighting of subjective values and the use of simple heuristics. The current paper analyzes 14 choice anomalies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
258
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 210 publications
(280 citation statements)
references
References 81 publications
(204 reference statements)
9
258
2
Order By: Relevance
“…Previous studies of the decisions based on past experience focus on binary choice tasks. These studies document a tendency to underweight rare events and highlight the descriptive value of models that assume reliance on small samples (Barron & Erev, 2003;Hertwig, Barron, Weber, & Erev, 2004;Erev et al, 2017;Erev & Haruvy, 2016;Rakow & Newell, 2010; and see related discussion in Osborne & Rubinstein, 1998).…”
Section: Experimental Studiesmentioning
confidence: 94%
“…Previous studies of the decisions based on past experience focus on binary choice tasks. These studies document a tendency to underweight rare events and highlight the descriptive value of models that assume reliance on small samples (Barron & Erev, 2003;Hertwig, Barron, Weber, & Erev, 2004;Erev et al, 2017;Erev & Haruvy, 2016;Rakow & Newell, 2010; and see related discussion in Osborne & Rubinstein, 1998).…”
Section: Experimental Studiesmentioning
confidence: 94%
“…One possibility is that rather than an "either/or", the notion of a bias toward extreme outcomes and some form of diminishing sensitivity are required to explain the results. Assuming that choices in risky decisions from experience follow a (evidently) biased (for example, due to underweighting of rare events, see Hertwig & Erev, 2009) multiplicative integration (i.e., expected value calculation) of observed outcomes and learned probabilities (see Erev, Ert, Plonsky, Cohen, & Cohen, 2017;Gonzalez & Dutt, 2011), then a choice bias for the extreme events can be manifested either on the numerical value of the outcome (i.e., utility function), or the objective probabilities (i.e., probability weighting function), or it can affect both.…”
Section: Potential Explanations and Future Directionsmentioning
confidence: 99%
“…Regret theory (Loomes & Sudgen, ) demonstrates that when choosing between two alternatives, individuals are sensitive to the possibility of regretting forgoing one of the options. Erev, Ert, Plonsky, Cohen, and Cohen () extended this research and showed that experienced regret slows learning. In the current context, variability in the cost of a safety measure implies that people who pay a high cost for taking a safety measure are likely to regret this choice later, when the cost is reduced (even when paying high cost is the optimal choice).…”
Section: Introductionmentioning
confidence: 78%
“…In order to evaluate this “prechoice experience” explanation, we chose to use data collected by Erev et al (). The participants in Erev et al's studies faced each problem for 25 trials and had to choose between a safe option (getting an outcome with certainty) and a risky option (a gamble).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation